Analysis of the Influence of Corn Plantation Potential on Farmer Income in Tang Village, Kecamatan Bokat, Buol District (A Case Study of Corn Farmers in Tang Village, Bokat District, Buol Regency) - Ramlawati; Hilmi (Journal of Sustainable Development Science, 2021)
This study aims to determine and analyze the potential effect of corn plantations on farmer income in Tang Village, Bokat District, Buol Regency. This study uses a quantitative research design. The data source is in the form of primary data, namely data obtained through interviews, and documentation related to this research. The data analysis technique used is multiple linear regression. Based on the results of the research and discussion, it can be concluded that the variables of land area, production costs, labor, and selling prices simultaneously have a positive and significant effect on the income of corn farmers in Tang Village, Bokat District, Buol Regency. The results of the research partially show that the selling price variable has a positive and significant effect on the income of corn farmers in Tang Village, Bokat District, Buol Regency, while the variables of land area, production costs, and labor have a positive but not significant effect on the income of corn farmers in Tang Village, Bokat District. Buol Regency.